A importância da modalização em quatro manifestos produzidos pela UMAR - Aouto, Ana (Mulheres no Discurso - Women in Discourse, 2025)
This article seeks to highlight the instrumental role played by the “manifesto” genre of discourse in the combative culture of the Portuguese feminist association UMAR, which, since its inception, has used manifestos both to call for change and to point out ways forward. Specifically, the article focuses on some examples of the construction of modalization in four manifestos produced by the association with the aim of ascertaining what role modalization plays in the art of questioning, criticizing and convincing. The analysis of modalization in UMAR's manifestos highlights the central role of language as an instrument of social and political intervention. In the texts analyzed, modalization is used to express opinions, argue, confront and call for action, supporting a discourse of denunciation and utopian construction. There is an articulated use of epistemic modalization, which modulates degrees of certainty and authority, and deontic modalization, which imposes moral obligations and calls for collective responsibility. These linguistic mechanisms not only support the argumentativeness of the texts, but also project ideologies and construct meanings that oscillate between criticizing the present and calling for a more egalitarian and inclusive future.